Features of dermatofibroma in reflectance confocal microscopy - Pogorzelska‐Antkowiak, Anna; Wcisło‐Dziadecka, Dominika; Brzezińska‐Wcisło, Ligia; Pawlicki, Krzysztof; Antkowiak, Ryszard; Corneli, Paola (International journal of dermatology, 2020)
Background Dermatofibroma (DF) is a common benign skin lesion in a majority of cases located on the legs or upper limbs. The etiology of DF is still unclear. Objectives Reflectance confocal microscopy features of DF were described. Methods Forty patients with DF diagnosis confirmed by dermoscopy were examined using reflectance confocal microscopy VivaScope 1500 from March 2018 to April 2019. Results DF was more common in females (80%) than males (20%). Thirty‐six lesions (90%) were located on the limbs while four (10%) were on the trunk. Dermoscopically, 18 lesions (45%) revealed typical features: central white area with a brown network in the periphery. Twenty‐two DFs (55%) were found with a central white patch and globular‐like structures, surrounded by a thin brown network. In reflectance confocal microscopy, all revealed a typical honeycombed pattern, although in some cases (30%), streaming was observed. In two lesions (5%) in epidermis, few dendritic cells were observed, and one DF revealed roundish pagetoid cells (2.5%). The dermoepidermal junction (DEJ) in all lesions was abounded in dilated vessels. The most common observable feature of DF was bright “rings” composed of monomorphic, regular cells surrounding dark dermal papillae. In five lesions (12.5%), rings were “double” because of exceptionally pigmented DF. Conclusion Reflectance confocal microscopy enables us to describe microscopic features of DF. There are four confocal microscopic features observable in each DF: in the epidermis, normal honeycombed pattern, sometimes with local streaming, in DEJ, edged papillae, bright rings, and dilated vessels.